The effect of ankle kinesio taping on ground reaction force components in individual with ankle sprain during walking - Nazarioloum, S.; Hoseini, Y.; Bagheri, S. (Journal of Advanced Sport Technology, 2020)
Ankle sprain is one of the most common injuries in different population. One way to treat ankle sprain is to use a Kinsio tape. Given the importance of the ground reaction forces, no research has been done on the effect of the kinesio tape on the components of the ground reaction force. Therefore, in this study, we intend to investigate the effect of Kinsio Tape on the components of ground reaction force. 10 females with ankle sprain participated in this study. Using a force plate (1000 Hz), the components of the ground reaction force were measured while walking in two conditions with and without tape. Then, the peak variables of the ground reaction forces, impulse, and loading rate were extracted. The repeated measure test with a significance level (P =0.05) was used for statistical analysis. The results showed that the use of kinesio tape significantly reduced the components of ground reaction force in the direction of Fz1(p = 0.01), Fx1 (p = 0.027) and Fy1 (p = 0.001), but in the other components there was no difference between the two conditions. According to the results of the present study, it seems that Kinesio Tape cannot provide sufficient mechanical support to improve the condition of the ankle, so the use of Kinesio Tape for treatment is ambiguous.